Raw data of air hydrate properties of the EDML ice core - Florian Painer; Ilka Weikusat; Sepp Kipfstuhl (PANGAEA, 2025)
In the deeper part of polar ice sheets, air hydrates are the primary air inclusions. They trap most of the ancient air molecules used for paleoclimatic reconstructions in their crystal structure. Furthermore, their number and size was found to correlate with past climate. This dataset presents the raw data of air hydrate parameters of the EPICA Dronning Maud Land (EDML) ice core from 1255 m to 2771 m depth. Air hydrate parameters were measured and analyzed in 74 ice thick section microphotographs using digital image analysis. The images were analyzed by Florian Painer at the Alfred Wegener Institute, Bremerhaven and the analysis routines were implemented in Python using open-source libraries. The aim was to develop a semi-automated analysis routine and to provide a high-resolution record of air hydrate properties of the EDML ice core. In total, about 183.000 air hydrates were segmented from the microphotographs and analyzed using digital image analysis. The microphotographs were obtained in the years 2002 - 2006 during the Antarctic field season, shortly after the sample was drilled, using an optical microscope (Kipfstuhl et al., 2006; Kipfstuhl, 2007).